The legend of Zelda. Twilight princess. 2 - Himekawa, Akira; Stan!, 1964- (VIZ Media, 2017)
In ancient times, the Spirits of Light sealed a band of wizards inside the Twilight Realm to punish them for trying to overtake the realm of Hyrule. Their power was sealed away in the Shadow Crystal, but now, an evil menace is trying to find Midna, the Twilight Princess, in order to put the Shadow Crystal together again in order to rule both the Twilight Realm and the World of Light. The hero Link wakes up in the Twilight Realm in the shape of a wolf and is tasked with finding the shards of the Shadow Crystal first.